2010
DOI: 10.1111/j.1526-4637.2010.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Dietary Agmatine Sulfate in Lumbar Disc-associated Radiculopathy. An Open-label, Dose-escalating Study Followed by a Randomized, Double-blind, Placebo-controlled Trial

Abstract: Objective. Agmatine, decarboxylated arginine, was shown in preclinical studies to exert efficacious neuroprotection by interacting with multiple molecular targets. This study was designed to ascertain safety and efficacy of dietary agmatine sulfate in herniated lumbar disc-associated radiculopathy. Study Design. First, an open-label dose escalation study was performed to assess the safety and side-effects of agmatine sulfate. In the follow-up study, participants diagnosed with herniated lumbar disc-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 68 publications
1
44
0
Order By: Relevance
“…AGM possesses an insulin-like action; it increases insulin release from pancreatic islet β-cells and decreases advanced glycated end products that control many of diabetic complications (Piletz et al 2013). AGM is considered to be safe when used for prolonged periods of time in humans (Keynan et al 2010;Gilad 2013, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…AGM possesses an insulin-like action; it increases insulin release from pancreatic islet β-cells and decreases advanced glycated end products that control many of diabetic complications (Piletz et al 2013). AGM is considered to be safe when used for prolonged periods of time in humans (Keynan et al 2010;Gilad 2013, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…The agmatine sulfate powders or pills generally contain 250-750 mg agmatine sulfate per serving where daily intake can be up to 7500 mg/ day. 35 There are limited studies or case reports which stated that long-term agmatine use is safe in humans. 23,35 In one case, a daily dose of 2.67 g oral agmatine sulfate for 5 years was reported to be safe without evidence of any adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…35 There are limited studies or case reports which stated that long-term agmatine use is safe in humans. 23,35 In one case, a daily dose of 2.67 g oral agmatine sulfate for 5 years was reported to be safe without evidence of any adverse effects. The authors indicated that the periodic physical examinations and laboratory analyses revealed no adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imidazoline I 2 receptor ligands such as the purported endogenous I 2 receptor ligand, agmatine, and the selective synthetic I 2 receptor agonist, CR4056, have robust antihyperalgesic activity in animal models of inflammatory and neuropathic pain [4][5][6]. Agmatine is also effective in alleviating pain and facilitate recovery in humans suffering from lumbar disc-associated radiculopathy [7], and CR4056 is in the process of phase I clinical trial for neuropathic pain [4].…”
Section: Introductionmentioning
confidence: 99%